Simulation of the Load Evolution of an Anchoring System under a Blasting Impulse Load Using FLAC3D - Xigui Zheng; Jinbo Hua; Nong Zhang; Xiaowei Feng; Lei Zhang (Shock and Vibration)
A limitation in research on bolt anchoring is the unknown relationship between dynamic perturbation and mechanical characteristics. This paper divides dynamic impulse loads into engineering loads and blasting loads and then employs numerical calculation software FLAC3D to analyze the stability of an anchoring system perturbed by an impulse load. The evolution of the dynamic response of the axial force/shear stress in the anchoring system is thus obtained. It is revealed that the corners and middle of the anchoring system are strongly affected by the dynamic load, and the dynamic response of shear stress is distinctly stronger than that of the axial force in the anchoring system. Additionally, the perturbation of the impulse load reduces stress in the anchored rock mass and induces repeated tension and loosening of the rods in the anchoring system, thus reducing the stability of the anchoring system. The oscillation amplitude of the axial force in the anchored segment is mitigated far more than that in the free segment, demonstrating that extended/full-length anchoring is extremely stable and surpasses simple anchors with free ends.